Correction: Electrochemical biosensor for detection of 17β-estradiol using semi-conducting polymer and horseradish peroxidase. Issue 45 (20th July 2020) - Spychalska, Kamila; Zając, Dorota; Wiatrowska, Aleksandra; Cabaj, Joanna
Abstract : Correction for 'Electrochemical biosensor for detection of 17β-estradiol using semi-conducting polymer and horseradish peroxidase' by Kamila Spychalska et al., RSC Adv., 2020, 10, 9079–9087, DOI: ; 10.1039/C9RA09902F .